IMPLEMENTASI METODE INKUIRI PADA MATA PELAJARAN PAI DAN BUDI PEKERTI DI SMPIT AS SALAM MALANG - Ardian Aulia Rachman; Dwi Fitri Wiyono; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The inquisition method is a learning method that as a whole involves the ability of students to search and determine systematically, critically and analytically so as to be able to solve the intended problem or the findings in question with confidence. Learning at SMP IT As Salam Malang City itself is generally not optimal and satisfactory for Islamic religious education subjects which are still very far from what is expected. This research uses qualitative research and field research with interview and observation data collection techniques. The results showed that the steps for the implementation of the inquiry method in PAI learning at SMP IT As salam, Malang, were; orientation, finding hypotheses, collecting data, testing hypotheses and formulating conclusions. And the results of the implementation of this inquiry method can increase learning motivation so that students are active in the learning process and improve critical thinking skills where students are more daring to ask questions. In using this method, of course, there are drawbacks where students become less active in learning because in finding the problem they experience errors, while the advantages are very much needed where the motivation for activeness increases and equips students to handle new situations.